(untitled) (International journal of artificial intelligence, 2026)
Sesame (Sesamum indicum L.) is one of the most valuable oilseed crops cultivated in arid and semi-arid regions due to its high oil content, drought tolerance, and adaptability to saline soils. In the Republic of Karakalpakstan, increasing demand for vegetable oil and the need for sustainable agricultural production require the introduction of highly productive sesame varieties adapted to local environmental conditions. This study analyzes the possibilities of increasing oil yield through the selection of sesame varieties belonging to different ripening groups under the soil-climatic conditions of Karakalpakstan. Special attention is paid to early-, medium-, and late-ripening varieties, their biological characteristics, adaptability, and productivity indicators. The research demonstrates that correct selection of varieties according to ripening duration significantly influences seed yield, oil accumulation, and economic efficiency. Early-ripening varieties are characterized by rapid maturation and reduced exposure to drought stress, while medium- and late-ripening varieties possess higher biomass accumulation and oil productivity under favorable irrigation conditions. The study also highlights the importance of sowing time, irrigation regime, and varietal adaptability in improving oil yield.